Effect of Proportion of Aloe Vera Porridge with CMC (Carboxy Methyl Cellulose) Concentration on Characteristics of Ice Cream - Misbachul Ulum; Lukman Hudi; Rima Azara (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of the proportion of aloe vera with CMC concentration on the characteristics of ice cream. This study used a factorial Randomized Block Design (RAK) with 2 factors and was repeated 3 times. The first factor is the concentration of aloe vera pulp with 3 levels, namely: L1 = 40% aloe vera pulp, L2 = 30% aloe vera pulp, L3 = 20% aloe vera pulp. The second factor is the concentration of the stabilizer CMC (Carboxy Methyl Cellulose) with 3 levels, namely: C1 = 0.0% CMC, C2 = 0.1% CMC, and C3 = 0.2% CMC. The variables observed in this study were the analysis of vitamin C levels, viscosity, melting rate, physical color. analysis of total dissolved solids (TPT) and organoleptic tests (taste, aroma, and texture). The data obtained were analyzed using analysis of variance, if the results of the analysis showed significant differences, it would be continued with the 5% level of Real Difference Test (BNJ), for organoleptic tests were analyzed using the Friedman test. Based on the data obtained, the best treatment was aloe vera ice cream with 20% aloe vera pulp treatment and 0.2% CMC concentration (L3C3) which showed 0.14% vitamin C, total soluble solids 29.47°Brix, viscosity 107, 33 mPas, the value of lightness color is 81.91, the value of redness is -2.93, the value of yellowness is 24.51, the melting rate is 87.09 minutes, the organoleptic color is 3.73 (usually - like), the organoleptic aroma is 3.50 (usually - like) ), organoleptic texture 3.93 (like - very like), organoleptic taste 4.00 (like very much).